2016
DOI: 10.1111/nhs.12257
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, anxiety, and heart rate variability among nurses working different shift systems in Taiwan

Abstract: This cross-sectional comparative study investigated the levels of insomnia, anxiety, and heart rate variability of nurses members working different shift systems. One hundred and twenty-four participants were recruited from members of the nurses of two Taiwanese hospitals. Data were collected using the Chinese versions of the Athens Insomnia Scale and Beck Anxiety Scale questionnaires and electrocardiograms recorded immediately upon completion of each participant's work shift. A binary logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
6
21
1
3
Order By: Relevance
“…The estimates were also higher than those reported in other studies that used a different instrument for the assessment of depression (overall: 10%-40%) (Letvak et al, 2012;Nourry, Luc, Lefebvre, Sultan-Taïeb, & Béjean, 2014;Ohler, Kerr, & Forbes, 2010;Ruggiero, 2005). Furthermore, the proportion of nurses who had symptoms of anxiety (66% overall) was higher than other studies; earlier studies showed prevalence estimates below 38% (Hegney et al, 2014;Shen et al, 2016). Our study found that 38% of nurses reported symptoms of stress.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The estimates were also higher than those reported in other studies that used a different instrument for the assessment of depression (overall: 10%-40%) (Letvak et al, 2012;Nourry, Luc, Lefebvre, Sultan-Taïeb, & Béjean, 2014;Ohler, Kerr, & Forbes, 2010;Ruggiero, 2005). Furthermore, the proportion of nurses who had symptoms of anxiety (66% overall) was higher than other studies; earlier studies showed prevalence estimates below 38% (Hegney et al, 2014;Shen et al, 2016). Our study found that 38% of nurses reported symptoms of stress.…”
Section: Discussioncontrasting
confidence: 76%
“…Unfortunately, almost nothing is known about depression among expatriate nurses in Saudi Arabia, although it is quite high (13%–20%) among other expatriate groups (Al‐Maskari et al, ; Nadim et al, ). A few studies are available on anxiety and stress among nurses; prevalence of anxiety and stress in these studies ranged between 12% and 38% (Hegney et al, ; Shen, Yen, Yang, & Lee, ) and between 68% and 84%, respectively (Almajwal, ; Karkar, Dammang, & Bouhaha, ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical nurses'low mental health directly affects nurses' physical health [10], occupational satisfaction and sense of achievement, but also reduces work efficiency and quality [11]. Consequently, it can induce patient's negative emotions to treatment and the quality of service of hospital [12].…”
Section: Mental Health Education Practicementioning
confidence: 99%
“…Furthermore, a stronger association of SDs has been observed with rotating shifts than with day or night shifts (Shen et al . ). Certain treatments were studied for reducing insomnia in nurses, such as light exposure (Huang et al .…”
Section: Introductionmentioning
confidence: 97%